Penerapan Model Membaca Total untuk Meningkatkan Keterampilan Membaca Pemahaman Isi Teks dalam Menentukan Pokok Pikiran Siswa Kelas IV SDN I Cikulak Kabupaten Cirebon - Badar, Rohmatun Nurul; Sunarya, Dede Tatang; Gusrayani, Diah (Jurnal Pena Ilmiah, 2019)
Classroom Action Researchqis conducted to correctoa problem that occurs inrthe classroom. The problem thatpwas corrected in thiswstudy was the problem with readingwcomprehension skills in nonfiction storywmaterial. Efforts for improvementqare carried out in accordancekwith what the researcherhhas analyzed from therresearch conducted. Improvements are madeito improve planning, implementation,wstudent activities, and studentllearning outcomes. The subjects in this studylwere fourth grade students of SDN I Cikulak, Kecamatan5Waled, KabupatenvCirebon. Based on thekresearch conducted, the application ofjthe Total Reading Model has increasedkfor the teacher's performance in the planningjcycle 81.1%, cycle II 92.8%, cycle III 100%. For teacher performance, the implementation stage ofkthe first cycle is 78.6%, cycle II is 90.5%, cycle III is 100%. For student activities the criteriadare very good, first cycle 8%, cycle II 36%, cycle III 92%. For the first cycledlearning outcomes 40%, second cycle 68%, cycle III 92%. By looking at therresults of the study, there is an increasejin each cycle. Increases occur becausekof improvements in eachncycle. Thus it can be proven thatlthe application of the total readinglmodel can improve therresults of reading skills understandingkthe content of the text in determining the subjectmmatter. Keywords: total reading model, readingvcomprehension, reading skills.